2012
DOI: 10.1063/1.4757974
|View full text |Cite
|
Sign up to set email alerts
|

Eigen-like hydrated protons traveling with a local distortion through the water nanotube in new molecular porous crystals {[MIII(H2bim)3](TMA)·20H2O}n (M = Co, Rh, Ru)

Abstract: In molecular porous crystals {[M(III)(H(2)bim)(3)](TMA)·20H(2)O}(n) (M = Co, Rh, Ru), the structural property of confined water network and the dynamics of mobile hydrated protons have been examined by the measurement of infrared spectrum and microwave conductivity. The water network undergoes first order phase transition from the ice nanotube (INT) to the water nanotube (WNT) around 200 K, while the infrared spectral features for these states are almost equivalent. Consequently, the water molecules in WNT dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…The formation of such hydrated protons has been studied in detail in acidic aqueous solutions (such as HCl), organic membranes, and protonated water clusters in the gas phase 19. For crystals of {[Co III (H 2 bim) 3 ] ⋅ (TMA) ⋅ 20 H 2 O} n ( 1 ; H 2 bim=2,2′‐biimidazole, TMA=trimesate), the crystal structure of the WNT and the proton‐transfer dynamics have been examined by infrared (IR) spectroscopy measurements 20. At a temperature of about 243 K, the confined WMC underwent a first‐order phase transition from a frozen ice nanotube (INT) to a melted water nanotube (WNT), while the IR spectra of the two WMCs were nearly equivalent; it was concluded that H 2 O in the WNT thermally fluctuates around defined positions in the INT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of such hydrated protons has been studied in detail in acidic aqueous solutions (such as HCl), organic membranes, and protonated water clusters in the gas phase 19. For crystals of {[Co III (H 2 bim) 3 ] ⋅ (TMA) ⋅ 20 H 2 O} n ( 1 ; H 2 bim=2,2′‐biimidazole, TMA=trimesate), the crystal structure of the WNT and the proton‐transfer dynamics have been examined by infrared (IR) spectroscopy measurements 20. At a temperature of about 243 K, the confined WMC underwent a first‐order phase transition from a frozen ice nanotube (INT) to a melted water nanotube (WNT), while the IR spectra of the two WMCs were nearly equivalent; it was concluded that H 2 O in the WNT thermally fluctuates around defined positions in the INT.…”
Section: Introductionmentioning
confidence: 99%
“…[19] For crystals of {[Co III -(H 2 bim) 3 ]·(TMA)·20 H 2 O} n (1; H 2 bim = 2,2'-biimidazole, TMA = trimesate), the crystal structure of the WNT and the proton-transfer dynamics have been examined by infrared (IR) spectroscopy measurements. [20] At a temperature of about 243 K, the confined WMC underwent a first-order phase transition from a frozen ice nanotube (INT) to a melted water nanotube (WNT), while the IR spectra of the two WMCs were nearly equivalent; it was concluded that H 2 O in the WNT thermally fluctuates around defined positions in the INT. Meanwhile, before the melting state via the first-order phase transition of 1, the INT exhibited a broadening endothermic transition.…”
Section: Introductionmentioning
confidence: 99%
“…200 K. 19 The absolute value at 270 K was approximately one order of magnitude smaller than the · MW value along the c axis, as previously reported for the WMC of 3. 20,21 In accordance with the phase transition, the reduction in the · MW just below T m = 197 K (broken line) became slightly steeper than the curve of activation behaviour. In contrast, such thermal activation behaviour was never observed in the · MW perpendicular to the c axis (green solid circles), for which the absolute value was one order of magnitude smaller than the · MW parallel to the c direction at 270 K (red open circles).…”
Section: Resultsmentioning
confidence: 80%
“…A proton transfer via water networks has been widely studied, for instance, in water nanotubes and water chains confined in the hydrophilic nanochannel of molecular porous crystals [ 17 , 18 , 19 ]. The proton is affected by the size, geometry, and interfacial interaction arising from the framework molecules.…”
Section: Introductionmentioning
confidence: 99%